Service User- and Carer-Reported Measures of Involvement in Mental Health Care Planning: Methodological Quality and Acceptability to Users - Gibbons, Chris J.; Bee, Penny E.; Walker, Lauren; Price, Owen; Lovell, Karina (Frontiers in Psychiatry, 2014)
Abstract Background: Increasing service user and carer involvement in mental health care planning is a key healthcare priority, but one that is difficult to achieve in practice. To better understand and measure user and carer involvement it is crucial to have measurement questionnaires that are both psychometrically robust and acceptable to the end user. Methods: We conducted a systematic review using the terms ‘care plan$,’ ‘mental health,’ ‘user perspective$’ and ‘user participation’ and their linguistic variants as search terms. Databases were searched from inception to November 2012, with an update search at the end of September 2014. We included any articles that described the development, validation or use of a user and/or carer-reported outcome measures of involvement in mental health care planning. We assessed the psychometric quality of each instrument using the ‘Evaluating the Measurement of Patient-Reported Outcomes’ (EMPRO) criteria. Acceptability of each instrument was assessed using novel criteria developed in consultation with a mental health service user and carer consultation group. Results: We identified eleven papers describing the use, development and/or validation of nine user/carer reported outcome measures. Psychometric properties were sparsely reported and the questionnaires met few service user/carer-nominated attributes for acceptability. Where reported, basic psychometric statistics were of good quality, indicating that some measures may perform well if subjected to more rigorous psychometric tests. The majority were deemed to be too long for use in practice. Discussion: Multiple instruments are available to measure user/carer involvement in mental health care planning but are either of poor quality or poorly described. Existing measures cannot be considered psychometrically robust by modern standards, and cannot currently be recommended for use. Our review has identified an important knowledge gap, and an urgent need to develop ne